Does Egyptian Orange Exports Really have a Market Power in Saudi Arabia Market? - Mazrou, Yasser S. A (Asian Journal of Agriculture and Rural Development, 2015)
Egypt is one of the important orange exporters and Saudi Arabia also is an important import orange market. The Saudi orange market is a main market for Egypt which has a market share that exceeds half of Saudi orange market by 55.72%. This article aims to discover the degree of market power for Egyptian orange exports and other competitors in the Saudi market and if it is considered a measure of the relative mark- up by applying Residual Demand Elasticity approach. The results show that Egyptian orange exports has just a statistically signified market power by SUR and 3-SLS and has a negative sign, which may gain monopolistic profits by the relative mark-up over its marginal cost by about 63.7% without losing any of its market share. The source of Egyptian orange exports market power is due to: 1- product differentiation where Egypt exports navel orange most its export season compared with sweet orange which exported from other competitors. 2- Saudi Arabia Market demand characteristics which reflect on the consumers preference for Egyptian oranges.